Scleredema adultorum of Buschke in a child – a rare case - Pal, S; Dey, PK; Das, S; Pandey, S; Bagchi, NR (Journal of College of Medical Sciences-Nepal, 2014)
Scleredema adultorum of Buschke is a rare connective tissue disorder reported usually following streptococcal infection, influenza, measles, and mumps. This is a report of scleredema adultorum developing after streptococcal infection in an 10-year-old girl. The diagnosis was established by characteristic picture on skin biopsy using special stain. The patient had a benign course and responded to local emollients only. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 60-62 DOI: http://dx.doi.org/10.3126/jcmsn.v9i3.10225